SOME FEATURES OF WOMEN’S SOCIAL ACTIVITIES IN UZBEKISTAN (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
In Uzbekistan, there is a process of relations related to increasing the social activity of women and strengthening their position in society.